A review of the cultural competence view of cardiac rehabilitation - Davidson, Patricia; Gholizadeh, L.; Haghshenas, A.; Rotem, A.; Digiacomo, Michelle; Eisenbruch, M.; Salamonson, Y. (Blackwell Publishing, 2010)
Aims and objectives. This paper describes cultural competence issues within the scientific and scholarly discourse surrounding cardiac rehabilitation (CR). Background.CR is an important secondary prevention strategy, improving health-related outcomes and reducing the risks of subsequent cardiovascular events. Internationally, it is widely accepted as a discrete health service model and is endorsed by government and professional bodies. Over past decades, low participation rates in CR remain a concern, particularly among minority groups and culturally and linguistically diverse populations. Design. Systematic review. Methods. Search of electronic databases. Conclusions. Few studies to date have described cultural competence in CR service design and as a consequence, there are minimal data to assist CR professionals and policy makers in tailoring health service delivery models. The limited scholarly debate and discussion regarding cultural competence in the CR literature limits the development and evaluation of culturally appropriate interventions. Relevance to clinical practice. There needs to be greater attention to the concept of cultural competence, both in practice and research settings, to ensure access to CR for people from culturally and linguistically diverse backgrounds.